Phase Transition of Enstatite‐Ferrosilite Solid Solutions at High Pressure and High Temperature: Constraints on Metastable Orthopyroxene in Cold Subduction. Issue 12 (13th June 2020) - Xu, Jingui; Fan, Dawei; Zhang, Dongzhou; Guo, Xinzhuan; Zhou, Wenge; Dera, Przemyslaw K.
Abstract: (Mg, Fe)SiO3 orthopyroxene is an abundant mineral of oceanic subducting slabs. In‐situ high‐pressure and high‐temperature single‐crystal X‐ray diffraction has been used to investigate the phase transition of orthopyroxene across the enstatite‐ferrosilite (En‐Fs) join (En70 Fs30, En55 Fs45, En44 Fs56 and Fs100 ) up to 24.3 GPa and 800 K, simulating conditions within the coldest part of a subduction zone consisting of an old and rapidly subducting slab. Instead of the orthopyroxene → high‐pressure clinopyroxene transition, the α‐opx → β‐opx and β‐opx → γ‐opx phase transition are observed at 7.2–15.3 and 11.6–21.1 GPa (depending on the Fs content), respectively. This study indicates that the pressure‐induced phase transition of (Mg, Fe)SiO3 orthopyroxene under relatively low temperature (<800 K) could be different than those occurring under relatively high temperature (>800 K). Additionally, the α‐opx → β‐opx → γ‐opx phase transition could exist within the center of the extremely cold slabs (like Tonga), where such low temperature persists to ~600‐km depth. Plain Language Summary: (Mg, Fe)SiO3 is the most abundant chemical compound in Earth's mantle. Investigating its phase relations at high‐pressure and high‐temperature is of fundamental importance in constraining the composition and understanding the structure of the Earth's interior. Previous studies have well established the phase diagram of (Mg, Fe)SiO3 at high pressure and high temperature. Orthopyroxene is a low‐pressure phase; with increasing pressure and temperature, orthopyroxene transforms to the high‐pressure clinopyroxene, then, it transforms to akimotoite or decomposes to wadsleyite + stishovite. These phase transitions require temperatures higher than 900 K, which are easily satisfied in the normal mantle or relatively warm subduction zone conditions. However, extremely low‐temperature region exists in the center of some old and rapidly subducting slabs (e.g., Tonga), and such low‐temperature region (~800 K) can extend to ~600‐km depth. In this study, we investigate the phase relations of (Mg, Fe)SiO3 orthopyroxene with several different compositions to 24.3 GPa and 800 K. A different phase transition path is observed, that is, the α‐opx → β‐opx → γ‐opx at pressures within the transition zone depths. Therefore, the result of this study adds one more piece of information to our understanding of phase relations of (Mg, Fe)SiO3 orthopyroxene within the extremely cold subducted slabs. Key Points: Phase transition of MgSiO3 ‐FeSiO3 solid solutions was investigated to 24.3 GPa and 800 K using single‐crystal X‐ray diffraction Metastable orthopyroxene progressively transforms into the β‐opx and γ‐opx phase at high temperature (800 K) and high pressure Metastable orthopyroxene and its high‐pressure phases could exist within the coldest part of old slabs and contribute to slab stagnation